2021
DOI: 10.15586/aei.v49i2.46
|View full text |Cite
|
Sign up to set email alerts
|

Preconception exposure to over-the-counter medications and antibiotics and the risk of childhood asthma in Lebanon: A cross-sectional study

Abstract: Objective: The aim of this study was to elucidate the relationship between the mother’s use of over-the-counter (OTC) medications during pregnancy and asthma in Lebanese children. Methods: A cross-sectional study was conducted on Lebanese students in both public and private schools, between January and September 2017, involving 1000 children aged between 4 and 17 years. Results: The intake of any medication as an independent variable throughout pregnancy reveals that being in a public school compared to a priv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 52 publications
(70 reference statements)
0
10
0
Order By: Relevance
“…This inadequate control of the illness is associated with disease progression and poor QoL (19). In Lebanon, several studies were conducted on asthmatic patients that tackled the preschool asthma risk factor scale, evaluated association between different factors and both wheezing and asthma development, assessed asthma control, and evaluated the influence of diet and obesity on asthma (20)(21)(22)(23)(24)(25). However, data on patients' QoL is still scarce, particularly among adults (26).…”
Section: Introductionmentioning
confidence: 99%
“…This inadequate control of the illness is associated with disease progression and poor QoL (19). In Lebanon, several studies were conducted on asthmatic patients that tackled the preschool asthma risk factor scale, evaluated association between different factors and both wheezing and asthma development, assessed asthma control, and evaluated the influence of diet and obesity on asthma (20)(21)(22)(23)(24)(25). However, data on patients' QoL is still scarce, particularly among adults (26).…”
Section: Introductionmentioning
confidence: 99%
“…The data from the remaining 3 studies is presented in Table 3. For prenatal exposure, the ORs from the study by Malaeb et al 54 was 4.66 (1.92–11.30). Piler et al 55 found no association with prenatal and combined exposures while a mild association was seen with infant exposure on the outcome of pediatrician diagnosed asthma at 11 years of age.…”
Section: Resultsmentioning
confidence: 93%
“…Our results are consistent with those of a study showing that asthma is associated with exposure to the respiratory syncytial virus during infancy. 37 Studies have also shown that viral infections of the lower respiratory tract alter the development of the respiratory/ immune system, increasing the likelihood of developing asthma, specifically in predisposed children. 49,50 As for the hygiene hypothesis, to the best of our knowledge, this study is the first to use a validated scale to assess the association between the hygiene hypothesis theory and asthma in preschool children.…”
Section: Discussionmentioning
confidence: 99%
“…The third section included questions related to factors generally associated with asthma, namely parental asthma 36 ; prenatal exposure to medications (antibiotics, paracetamol) 36,37 ; alcohol use 38 and smoking 39,40 during pregnancy; preterm delivery 41 ; passive smoking and environmental exposure to toxicants 39,40 ; number of older siblings; medication or alcohol intake during breastfeeding; reflux; atopy; exposure to pesticides (occupational, regional, local, and domestic) 39,40 ; and the use of cleaning products at home. 42 The exposure to pesticides was recorded using the following questions: ''Have you ever used pesticides in your work?…”
Section: Hygiene Measures and Asthmamentioning
confidence: 99%